Acoustic study of the influence of climate change on the propagation of noise generated by industrial units in real-time: by an industrial zone in Algeria - Arbaoui Iliace; Tadjeddine Ali Abderrazak; Hamiani Hichem; Hamou Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The industrial revolution in the field of gas and oil treatment that has known the Oran region-Algeria-has participated in the production and propagation of noise pollution and loud noises on the environment and around the places residential, for this, a multitude of noises are now part of our daily life. This contribution concerns the propagation of noise pollution in the industrial environment and the effects caused by atmospheric pollution which has a great influence on the phenomenon of planetary climate change and on meteorological parameters, the latter having a great influence on the propagation of noise. Our study is part of the objective of evaluating the noise levels emitted by gas installations in the industrial zone of ArzewOran, and of seeing the effects of the variation of meteorological parameters on the propagation of noise. To do this, we have adopted a precise in-situ methodology. Subsequently, for the processing of the measurement results, we opted for the COD-TYMPAN software in real-time as a calculation tool to interpret our results